2020
DOI: 10.7717/peerj.9324
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and bonding strength of chromium species by ferrihydrite from acidic aqueous solutions

Abstract: The adsorption behavior of Cr(III) and Cr(VI) ions onto laboratory-synthesized 2-line ferrihydrite was investigated under a batch method as a function of initial chromium concentration (0.1–1000 mg L−1) and pH (3.0 and 5.0). Moreover, the effect of the type of anion (chloride and sulfate) on Cr(III) adsorption was studied. The affinity of Cr(III) ions for the ferrihydrite surface depended on both the type of anion and pH of the solution and the maximum adsorption capacities decreased as follows: q (SO42−, pH 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 72 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…13). This observation is consistent with findings reported in previous studies on other substrates 25,51,52 ) depending on the pH and total [Cr(VI)]. 50,[53][54][55] In low pH media (< 6), Cr(VI) exists as a distribution of HCrO 4 − and Cr 2 O 7 2− with the former favored for total [Cr(VI)] < 10 −2 M. In contrast, Cr(VI) speciates entirely as CrO 4 2− at higher pH (> 7) regardless of concentration.…”
Section: Discussionsupporting
confidence: 94%
“…13). This observation is consistent with findings reported in previous studies on other substrates 25,51,52 ) depending on the pH and total [Cr(VI)]. 50,[53][54][55] In low pH media (< 6), Cr(VI) exists as a distribution of HCrO 4 − and Cr 2 O 7 2− with the former favored for total [Cr(VI)] < 10 −2 M. In contrast, Cr(VI) speciates entirely as CrO 4 2− at higher pH (> 7) regardless of concentration.…”
Section: Discussionsupporting
confidence: 94%
“…Using the Sips isotherm to model the obtained experimental data leads to a parameter 1/ n s value deviated from unity, suggesting the heterogeneity of the adsorbent surface [ 68 ]. Regardless of the extractant used for functionalization, the Sips model better describes the adsorption process, reflected by the highest correlation coefficient (R 2 ) values.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies agree that the adsorption of HCrO 4 − onto α-Fe 2 O 3 involves the formation of a surface complex [47,52,56,57]. It was suggested that HCrO 4 − may have undergone ligand exchange with the surface hydroxyl groups of α-Fe 2 O 3 , ultimately forming an inner sphere surface complex [52], as represented in Eq.…”
Section: Adsorptive Removal Of Cr(vi) By α-Fe 2 O 3 Nanobladesmentioning
confidence: 87%